Association of Sexual Maturation and Body Size of Arfak Children - ELDA IRMA JEANNE JOICE KAWULUR; BAMBANG SURYOBROTO; SRI BUDIARTI; ALEX HARTANA (Bogor Agricultural University, Indonesia, 2012)
Gonad maturation in pubertal girls and boys is accompanied with somatic growth spurt, changes in quantity and distribution of body fat (BF), development of secondary sex characters, and relevant physiological events. Menarche (first event of menstruation) and spermarche (first event of nocturnal sperm emission) are usually used as indicators of gonad maturation. We found that median age at menarche of Arfak girls in Manokwari, West Papua is 12.2 years, while median age at spermarche of boys is 13.6 years. A possible factor causing young age at menarche is due to adaptation to unstable environmental conditions because of high risk of mortality by malaria disease during childhood. The events of menarche and spermarche achieved one year after the peak body height (BH) velocity, and just before or at the same time with the time of maximum growth rate of body weight (BW), body mass index (BMI), and BF. The average BMI of Arfak girls was big at 21.9 kg/m2 at the time of their menarche. Bigger average BMI might be caused by prepubertal slowing down of BH growth compare to growth of BW whichis still increasing. Girls accumulate BF before puberty to be used as an energy reserve for the occurrence of menarche. At the time of development of secondary sexual characters girls use the fat reserve so it decline sharply after puberty. In boys, growth rate of BF was stopped at 11 years old, and then growing negatively presumably because boys use fat mass for the occurence of spemarche. BF growth rate reached the lowest point at the age 16 years old, and then increase linearly with age through adolescence until adulthood at age 23 years old.